Analisis Pengaruh Struktur Modal, Kebijakan Deviden, Dan Kinerja Keuangan Terhadap Nilai Perusahaan Sektor Telekomunikasi Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2022 - Henitha Nadia Kristy; Hwihanus Hwihanus (Jurnal Akuntan Publik, 2024)
This research aims to analyze the relationship between capital structure, dividend policy, financial performance and company value in the telecommunications industry. This research uses quantitative methods and applies secondary data. The research results show that capital structure, dividend policy and financial performance greatly influence company value. In other words, making decisions about capital structure, dividend policy, and financial performance can positively influence increasing company value. In other words, the results of this research can be used by practitioners and decision makers in the telecommunications industry to help them increase the value of their business.